DV-Hop Localization Algorithm for Underwater Wireless Sensor Networks based on Squirrel Algorithm Optimization - Zhang, Wenkang; Mao, Yuming; Hu, Huizhong (International Journal of Mechanical and Electrical Engineering, 2025)
Aiming at the problem of large errors in the positioning algorithm of underwater wireless sensor networks, an underwater DV-Hop positioning algorithm optimized based on the squirrel algorithm is proposed. The estimated position of the unknown nodes in the DV-Hop algorithm is optimized by the squirrel algorithm, and optimization is carried out with the squirrel algorithm, the number of hops between nodes is optimized using the hop count adjustment factor, the beacon nodes that will lead to a large error are removed by the use of the covariance degree, and the average hopping distance of beacon nodes is optimized using the weighted processing method, and the average value of the improved average hopping distance is taken to be the average hopping distance of each unknown node, to Improve the localization accuracy of DV-Hop algorithm. The simulation results show that the improved algorithm improves the positioning accuracy by 34.02% and 9.75% compared with the traditional 3DDV-Hop and the hopping distance optimized 3DDV-Hop, respectively.